KRITIK ATAS KONTROVERSI HADIS TENTANG AURAT LAKI-LAKI - Faruq, Umar (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
This article discusses two seemingly contradictory hadith, is t tradition of male genitalia. There is a hadith which states that the thigh is including for male genitalia, so that should be covered, and there is another tradition that informs that the Prophet ever -in some circumstances-lifting clothes so it looks his thigh. This seems contradictory hadith then tried to reconcile with utilizing the science of hadith traditions that are concerned in this matter, namely mukhtalif al-hadîth. By the several methods of settlement, the authors take the methods of al-jam?. Under this settlement, it can be seen that the two traditions is basically not contradictory, both are maqbûl and ma?mul bih, prohibition to open thighs is makrûh tanzîh arbitrate and be open is allowed if there is an intent.